Exploring dementia management attitudes in primary care: a key informant survey to primary care physicians in 25 European countries - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2017)
Background: Strategies for the involvement of primary care in the management of patients with presumed or diagnosed dementia are heterogeneous across Europe. We wanted to explore attitudes of primary care physicians (PCPs) when managing dementia: (i) the most popular cognitive tests, (ii) who had the right to initiate or continue cholinesterase inhibitor or memantine treatment, and (iii) the relationship between the permissiveness of these rules/guidelines and PCP's approach in the dementia investigations and assessment. Methods: Key informant survey. Setting: Primary care practices across 25 European countries. Subjects: Four hundred forty-five PCPs responded to a self-administered questionnaire. Two-step cluster analysis was performed using characteristics of the informants and the responses to the survey. Main outcome measures: Two by two contingency tables with odds ratios and 95% confidence intervals were used to assess the association between categorical variables. A multinomial logistic regression model was used to assess the association of multiple variables (age class, gender, and perceived prescription rules) with the PCPs' attitude of trying to establish a diagnosis of dementia on their own. Results: Discrepancies between rules/guidelines and attitudes to dementia management was found in many countries. There was a strong association between the authorization to prescribe dementia drugs and pursuing dementia diagnostic work-up (odds ratio, 3.45; 95% CI 2.28-5.23). Conclusions: Differing regulations about who does what in dementia management seemed to affect PCP's engagement in dementia investigations and assessment. PCPs who were allowed to prescribe dementia drugs also claimed higher engagement in dementia work-up than PCPs who were not allowed to prescribe.
Keywords: Alzheimer's disease; dementia; primary care; GENERAL-PRACTITIONERS; DIAGNOSIS; CHALLENGES; DISCLOSURE